Effects of Corneal Stromal Lens Collagen Cross-Linking Regraft on Corneal Biomechanics - Rong Shi; Weize Wang; Yu Che; Shaorong Linghu; Taixiang Liu (Journal of Ophthalmology)
Background. Corneal collagen cross-linking (CXL) therapy, a method that uses a combination of riboflavin and ultraviolet-A light (UVA), can promote the formation of covalent cross-linking of amino acid residues of corneal collagen and enhance the hardness of the cornea. In this study, we explored the effects of corneal stromal lens collagen cross-linking regraft on corneal biomechanics. Methods. A total of 15 New Zealand white rabbits were divided into 3 groups: normal control group (group A), SMILE + uncross-linked lens implantation group (Group B), and SMILE + cross-linking lens implantation group (group C). The design parameters of SMILE surgery were as follows: the corneal cap was 120 um thick, the lens diameter was 6.5 mm, and the diopter was -6.0D. Riboflavin and ultraviolet-A (UVA) were used as corneal stromal lens CXL, which was implanted into the allogeneic rabbit corneal stromal bag 24 hours after the operation. Postoperative corneal thickness (CCT), refraction, AS-OCT, and corneal biomechanics were performed before and then at 1 and 3 months after the operation. Results. All corneas appeared transparent and smooth 3 months after surgery. The corneal thicknesses of both group B and group C were lower than those before the operation. The corrected refraction of group B and group C after lens implantation was also lower than the expected corrected power; there was no significant difference between the two groups (P>0.05). AS-OCT results showed an uneven surface and thickness of the corneal stromal lens in two eyes of group B. Moreover, corneal elastic deformation increased with intraocular pressure in each group; displacement from large to small was group B > group C and > group A. The creep from large to small was group B > group C > group A. The fiberboard layers of groups B and C were disordered, and there were a few autophagosomes in the fibroblasts of group B by transmission electron microscopy (TEM). Conclusions. Allograft graft of corneal stromal lens collagen cross-linked can significantly increase the biomechanical properties of the cornea.